Facile Esterification of Alcohols with 2-Acyl-4,5-dichloropyridazin-3(2H)-ones under Friedel–Crafts Conditions - Kim, Bo Ram; Sung, Gi Hyeon; Ryu, Ki Eun; Yoon, Hyo Jae; Lee, Sang-Gyeong; Yoon, Yong-Jin (Synlett, 2014)
This paper describes the esterification of aromatic and aliphatic alcohols by using 2-acyl-4,5-dichloropyridazin-3(2H)-ones as an acyl source under Friedel–Crafts conditions. Twelve alcohols were reacted with four 2-acyl-4,5-dichloropyridazin-3(2H)-ones in the presence of AlCl3 in tetrahydrofuran at room temperature to give the corresponding esters in moderate to excellent yields. Thus, 2-acylpyridazin-3(2H)-ones serve as good and atom-economic acyl sources for the esterification of aromatic alcohols under Friedel–Crafts conditions, representing a rapid, practical, and efficient method of esterification.
Keywords: acylation; esterification; Friedel–Crafts condition; sustainable chemistry; synthetic methods